2017
DOI: 10.3168/jds.2017-12700
|View full text |Cite
|
Sign up to set email alerts
|

Host-pathogen interactions in bovine mammary epithelial cells and HeLa cells by Staphylococcus aureus isolated from subclinical bovine mastitis

Abstract: Staphylococcus aureus is a common pathogen that causes subclinical bovine mastitis due to several virulence factors. In this study, we analyzed S. aureus isolates collected from the milk of cows with subclinical mastitis that had 8 possible combinations of bap, icaA, and icaD genes, to determine their capacity to produce biofilm on biotic (bovine primary mammary epithelial cells and HeLa cells) and abiotic (polystyrene microplates) surfaces, and their ability to adhere to and invade these cells. We also charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
(40 reference statements)
0
20
1
1
Order By: Relevance
“…Similar results were observed in a study conducted in Brazil, since they found that the strain with the largest production of biofilm presented the lowest invasion rate; whereas, the strain that showed poor biofilm formation had the highest invasion rate. However, they did not observe any relation between the invasion capacity and bap gene presence (65). Contrary to our finding, there are reports that did not find an association between capacity to produce biofilm and the invasiveness (23,66).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were observed in a study conducted in Brazil, since they found that the strain with the largest production of biofilm presented the lowest invasion rate; whereas, the strain that showed poor biofilm formation had the highest invasion rate. However, they did not observe any relation between the invasion capacity and bap gene presence (65). Contrary to our finding, there are reports that did not find an association between capacity to produce biofilm and the invasiveness (23,66).…”
Section: Discussioncontrasting
confidence: 99%
“…From a clinical point of view, there is a considerable relationship between the ability to form biofilms and resistance to conventional antibiotics (Sharma et al, 2019).According to the National Institute of Health, in humans, biofilms account for up to 80% of the total bacterial infections, including endocarditis, periodontitis, sinusitis, meningitis, osteomyelitis, chronic wounds, and prosthesis and implantable devices related infections (Khatoon et al, 2018). In many of these cases, infection arises from implantable medical devices, such as catheters, implants, and implantable electronic devices (Khatoon et al, 2018;Narayana and Srihari, 2019;Pelling et al, 2019) that become contaminated with bacteria, usually biofilms of staphylococci, streptococci, Gram-negative bacteria, and fungi (Kokare et al, 2009;Marks et al, 2014b;Rosini and Margarit, 2015;Gomes et al, 2016;Young et al, 2016;Castilho et al, 2017;Stewart and Bjarnsholt, 2020).…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…Mastitis, mainly caused by a microbial infection, is the inflammation of the breast parenchyma associated with lactation ( 1 ). In dairy cattle, mastitis, which causes swelling and pain in the udder and systemic inflammatory injuries, seriously affects animal health and reduces milk yield and quality, leading to considerable economic losses worldwide ( 2 ). Clinical bovine mastitis caused by Escherichia coli ( E. coli ) leads to endotoxin shock and death in extreme cases ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%